2-(4-Acetamidobenzenesulfonamido)-3-methylbutanoic acid - Sharif, S.; Iqbal, H.; Khan, I.U.; John, P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(13)H(18)N(2)O(5)S, the benzene ring and the acetamide group are almost coplanar [dihedral angle = 5.6 (3)degrees], and the amine group projects almost vertically from this plane [C-C-S-N = -84.5 (7)degrees]. A short intramolecular C-H center dot center dot center dot O contact occurs. In the crystal, O-H center dot center dot center dot O, N-H center dot center dot center dot O and N-H center dot center dot center dot(O,O) hydrogen bonds lead to a three-dimensional network. One of the methyl groups of the isopropyl residue is disordered over two orientations in a 0.747 (16):0.253 (16) ratio.